Consonant Substitution In Child Language (Ikwere) - Alerechi , Roseline (My University, 2018)
The Ikwere language is spoken in four out of the twenty-three Local Government Areas (LGAs) of Rivers State of Nigeria, namely, Port Harcourt, Obio/Akpor, Emohua and Ikwerre LGAs. Like Kana, Kalabari and Ekpeye, it is one of the major languages of Rivers State of Nigeria used in broadcasting in the electronic media. The Ikwere language is classified as an Igboid language of the West Benue-Congo family of the Niger-Congo phylum of languages (Williamson 1988: 67, 71, Williamson & Blench 2000: 31). This paper treats consonant substitution in the speech of the Ikwere child. It demonstrates that children use of a language can contribute to the divergent nature of that language as they always strive for simplification of the target language. Using simple descriptive method of data analysis, the paper identifies the various substitutions of consonant sounds, which characterize the Ikwere children’s utterances. It stresses that the substitutions are regular and rule governed and hence implies the operation of some phonological processes. Some of the processes are strengthening and weakening of consonants, loss of suction of labial implosives causing them to become labial plosives, devoicing of voiced consonants, etc. While some of these processes are identical with the adult language, others are peculiar to children, demonstrating the relationships between the phonological processes in both forms of speech. It is worthy of note that highlighting the relationships and differences will make for effective communication between children and adults.
Keywords: Divergent nature; phonological processes; rule governed